The pathway to diagnosis of dementia for Francophones living in a minority situation - Garcia, Linda J.; McCLeary, L.ynn; Emerson, Victor; Léopoldoff, Hélène; Dalziel, William; Drummond, Neil; Cohen, Carole; Koehn, Sharon; Silvius, James (The Gerontologist, 2014)
Purpose of the Study: As the prevalence of dementia increases, the pressure to make early diagnoses also increases. Although patients must be able to identify the symptoms to access appropriate services, they may not be equally accessible to all citizens in a multicultural society. Health care professionals and patients may lack a common “first language.” This study explores the experience of francophone persons with dementia (PWD) and their caregivers during the peri-diagnostic period. Design and Methods: Individual interviews were undertaken to elicit information regarding symptoms, the role of the family and friends, and the access to formal services. Seven PWD and their caregivers who spoke French as their primary language but who lived in a primarily English-speaking region completed the interviews. Results and Implications: No single symptom seemed sufficient to alert participants that dementia might be present. Participants communicated that there was a dire need to inform the public about the signs of dementia; they spoke of the role of the family physician and the importance of having a long-standing relationship with a health professional. For some, having similar personal characteristics, such as language and culture, might accentuate the strength of the relationship and facilitate the process of diagnosis.

Access to dementia services in a minority situation: The case of Francophones in Ontario [infographic] - Garcia, Linda; Chomienne, Marie-Hélène; Cadieux, M.-A.; Farmanova, E.; McCleary, L.; Molnar, F.; Agapitos, M.; Dalziel, W.; Khoury, L.; French-Merkley, V.; Joanisse, J. (2014)

Le potentiel d'offre et de demande de Services médicaux et diagnostiques dans la langue de communautés minoritaires : où se situe le français en Colombie-Britannique? - Giguère, Louis; Conway, Brian (Reflets, 2014)
Une étude comparative du potentiel de services médicaux dans les langues minoritaires de Colombie-Britannique révèle que des médecins non-francophones parlant français génèrent une retombée linguistique qui amplifie l’offre potentielle de services de santé et de services sociaux en français de façon dramatique. Ce mécanisme structurant s’appliquerait aux autres professions de la santé et des services sociaux, partout au Canada et il serait plus prononcé plus le contexte est minoritaire. Les communautés francophones doivent faire plus pour identifier, engager et outiller les professionnels et professionnelles « francophiles » et elles doivent élaborer une logique d’équité innovatrice pour dégager le potentiel d’offre de services de santé et de services sociaux en français dans un contexte multilingue. Mots-clés : CFASM, CLOSM, médecins parlant français, minorités linguistiques, équité, services d’interprétation, offre et demande

Le Centre de santé de Clare : un modèle pour l'accès à des services de santé en français - Sangaré, Yalla (Reflets, 2014)